Heavy Metal Pollution Studies of Soil from the Oti-Dompoase Dumpsite in Kumasi - Nkansah, Marian Asantewah; Kofi Adzibolosu, Anthony Seyram; Kumah, Moses Ernest; Bennin, Ernest; Adrewie, Dominic (Fine Chemical Engineering, 2024)
Waste disposal sites contribute a great deal to environmental pollution. The degree of pollution brought on by heavy metal contamination of soil collected from the Oti-Dompoase dump site in Kumasi of Ashanti region, Ghana was investigated in this study. Twelve (12) composite samples of the surface soil were taken in total at 10 cm depth from the dumpsite to conduct metal analysis. The measurement of heavy metal concentration was done utilizing Atomic Absorption Spectrometer, which uses the absorbance at various wavelength of the electromagnetic spectrum to determine the chemical identity of constituents of the sample and their concentrations with the help of standard solutions and Beer-Lambert law. The mean metal concentrations of soil samples were reported and arranged in terms of magnitude as follows: Iron (2,582.21 mg/kg) > Copper (348.50 mg/kg) > Lead (324.85 mg/kg) > Manganese (192.27 mg/kg) > Zinc (146.24 mg/kg) > Cadmium (7.06 mg/kg). Physiochemical properties such as electrical conductivity (EC), pH and organic matter and water content (%) were also investigated using a PHYWE electrical conductivity meter, pH meter and an oven, respectively. Most of the parameters analysed indicated pollution when compared to baseline values, while human exposure levels were within World Health Organization (WHO) standards. Assessments using geo-statistics of different hazard indicators, including pollution load index, contamination factor (CF), and geo-accumulation, all point to heavy metal pollution of the soil samples. Cadmium contamination was very high based on the pollution indices (CF, geo-accumulation, and pollution load) and manganese has the lowest level of pollution. There is limited data on the extent of pollution caused by the Oti-Dompoase dumpsite and this study will serve to fill this knowledge gap and contribute to the Millenium Development Goal seven (7) by providing data on the extent of pollution of soil around the Oti-Dompoase dumpsite and highlight the need for regular monitoring and on-site remediation strategies to safeguard the site to ensure environmental sustainability.